Molecular dynamics simulations of simplified sodium borosilicate glasses: the effect of composition on structure and dynamics. Issue 27 (5th July 2021) - Sahu, Pooja; Ali, Sk. Musharaf; Shenoy, K. T.; Mohan, Sadhana; Arvind, A.; Sugilal, G.; Kaushik, C. P.
Abstract : The fusion of valuable material properties has led to the acceptance of sodium borosilicate (NBS) glasses for nuclear waste immobilization. Abstract : The fusion of valuable material properties has led to the acceptance of sodium borosilicate (NBS) glasses for nuclear waste immobilization. Although popular, the mechanisms associated with these properties are still only partially discovered and need further exploration. Bearing this in mind, the combination of experiments, molecular dynamics (MD) simulations and the Dell, Yuan and Bray model have been used to understand the role of composition variation for structural and physical aspects of vitrified borosilicate glasses. Experiments have been conducted to evaluate the macroscopic glass parameters of density ( ρ ), glass transition temperature ( T g ) and thermal expansion coefficient (TEC). Experimentally observed trends for ρ, T g and TEC with composition have been found in good agreement with the MD results. MD studies also provide a microscopic understanding of the glass structure and phenomena associated with the change in the glass composition. A detailed view of local structure and medium-range connectivity for the borosilicate glasses has been explored. Owing to a large B4 population, the results showed the abundant presence of BO4 –BO4 connections, we hereby omit the generally accepted "B[4] avoidance rule" for glass. The relative propensity for connecting SiO4 /BO3 /BO4 structural motifs is in line with the predictions made by the Dell, Yuan and Bray model. Furthermore, the effects of composition on the mechanical integrity of NBS glasses, including the elastic nature, plastic distortion, yielding, breaking stress, and brittle fracture, have been explored by MD simulations. In addition, the glass dynamics have been evaluated by diffusion coefficient and the results suggest that Na + is likely to be more mobile in the case of NBS1 as compared to NBS2 and NBS3 due to significant disruption in the glass network introduced by a larger amount of Na2 O network modifier. Also, the diffusivity was reduced with increasing B2 O3 due to the altered role of Na + ions from network modifiers to charge compensators. The combined study of experiments, MD simulations and the Dell, Yuan and Bray model establish the correlation between the microscopic structure and macroscopic properties of NBS glasses with varied composition, which might be of great scientific use for future glasses in various applications including nuclear waste immobilization.